PENGARUH MEDIA PEMBELAJARAN E-LEARNING TERHADAP HASIL BELAJAR MAHASISWA PRODI PGSD UNIVERSITAS QUALITY BERASTAGI - Novi Tari Simbolon (JURNAL CURERE, 2021)
With this era of increasingly developing technology, learning programs are directed to be able to make better use of technology. One of the current uses of technology is e-Learning using the web to access it. There is no denying that many students now have smart phones, so it is easier to access them from wherever they are and at any time. Utilization of e-learning that is commonly developed today is using LMS (Learning Management System). Quality Berastagi University is one of the universities that have utilized e-Learning as a learning medium this semester. Learning activities using e-learning media on campus utilize the E-Learing application. In the learning process, students are given assignments by the lecturer and send the results of their reports via E-Learning. In addition, students are also given additional material in order to understand more broadly the material that may not be conveyed directly when face to face in class. E-learning is an alternative media to provide test exam questions and improvised media that do not always use print media. Based on the above phenomenon, it can be said that in the learning process, a method, strategy, media, or learning model is needed that can train students' abilities in improving learning outcomes, involving student activities optimally, and making mathematics learning more meaningful and fun. Lecturers are required to choose learning media that can stimulate the enthusiasm of each student to be actively involved in their learning experience. This study aims to determine student learning activities increase with E-Learning learning media in the PGSD Study Program, Quality Berastagi University.